Estabilidade paramétrica em sistemas hamiltonianos com um grau e meio de liberdade - Souza, Regivan Santos (2015)
In this thesis we present some of the theory of parametric stability in linear Hamiltonian systems with one degree and a degree and a half of freedom. To this end, we provide de nitions and results on Hamiltonian systems, symplectic vector spaces and linear stability of Hamiltonian systems balances. This work ends with the description of Deprit-Hori method in order to apply it to the Mathieu equation and thus build the boundary curves of the regions of stability and instability.